Effect of γ-Irradiation on Germination, Growth, Sensitivity and Survivability of Papaya cv. Kesar King - Murlee Yadav (Society for Promotion of Horticulture - Indian Institute of Horticultural Research, 2008)
An experiment was laid out in a 4x2 factorial design, with 4 levels of γ-irradiation (0,5,10&15 Krad) and two dates of sowing (15th September and 15th October) on papaya cv. Kesar King. The results indicated that germination percentage, survival percentage and plant growth increased with the increased in γ-irradiation upto 10 Krad. Early sowing of seed (15th September) showed better germination (73%), survival (70%) and plant growth as compared to late sowing (15th October). Interaction between γ-irradiation of 10 Krad and early sowing of seed (15th September) was found superior to all the other treatment combinations to obtain optimum germination percentage, survival percentage and plant growth.